DEPRESSÃO EM IDOSAS NÃO PARTICIPANTES DE ATIVIDADES GRUPAIS - Leite, Marines T.; Hildebrandt, Leila M.; Stumm, Eniva M. F.; Kirchner, Rosane M.; Battisti, Iara D. E.; Rieth, Giovani H.; Beienke, Flavio (Salão do Conhecimento, 2013)
Resumo